Kemampuan Komunikasi Matematis Siswa Kelas VIII pada Pola Bilangan melalui Pendekatan Realistic Mathematics Education (RME) - Nazira, Nazira; Yuhasriati, Yuhasriati; Elizar, Elizar (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2023)
Research on mathematical communication skills has a background on the importance of student's ability to organize ideas and thoughts when solving problems. This study aimed to determine students' mathematical communication abilities on number pattern material through learning with the RME approach at one of the Banda Aceh Middle Schools. The approach used in this research is descriptive qualitative. The subjects were 24 students, and three students were interviewed. Data was collected through interviews, which were analyzed in three stages: data reduction, data presentation, and drawing conclusions. The research showed that mathematical communication skills through learning with the RME approach for number pattern material experienced good development. Students in the high and medium categories can master drawing, written text, and mathematical expression indicators. Students in the low category can master drawing and mathematical expression indicators. The results showed that students experienced problems communicating mathematically in conveying ideas orally and in writing. As a result, an error occurred in solving the problem. This research is expected to be a reference for improving students' mathematical communication skills during the learning process.